Exercise-induced bone gain is due to enlargement in bone size without a change in volumetric bone density: a peripheral quantitative computed tomography study of the upper arms of male tennis players - Haapasalo, H.; Kontulainen, S.; Sievanen, H.; Kannus, P.; Jarvinen, M.; Vuori, I. (Bone, 2000)
Bilateral bone characteristics of the humerus (proximal, shaft, and distal sites) and radius (shaft and distal sites) in 12 former Finnish national-level male tennis players (mean age 30 years) and their 12 age-, height-, and weight-matched controls were measured with peripheral quantitative computed tomography (pQCT). The pQCT variables analyzed were bone mineral content (BMC), total cross-sectional area of bone (Tot.Ar), cross-sectional area of the marrow cavity (M.Cav.Ar), cortical bone (Co.Ar) and trabecular bone (Tr.Ar), volumetric density of cortical (Co.Dn) and trabecular (Tr. Dn) bone, cortical wall thickness (Co.Wi.Th), bone strength index (BSI), and principal moments of inertia (I(min) and I(max)). In the players, significant side-to-side differences, in favor of the dominant (playing) arm, were found in BMC (ranging 14%-27%), Tot.Ar (16%-21%), Co.Ar (12%-32%), BSI (23%-37%), I(min) (33%-61%), and I(max) (27%-67%) at all measured bone sites, and in Co.Wi.Th. (5%-25%) at the humeral and radial shafts, and distal humerus. The side-to-side M.Cav.Ar difference was significant at the proximal humerus (19%) and radial shaft (29%). Concerning the players' Co.Dn and Tr.Dn, the only significant side-to-side difference was found in the Co.Dn of the distal humerus, with the playing arm showing a slightly smaller Co.Dn than the nonplaying arm (-2%). In controls, significant dominant-to-nondominant side differences were also found, but with the majority of the differences being rather small, and significantly lower than those of the players. In conclusion, despite the large side-to-side differences in BMC, the volumetric bone density (Co.Dn, Tr.Dn) was almost identical in the dominant and nondominant arms of the players and controls. Thus, the players' high playing-arm BMC was due to increases in the Tot.Ar, M.Cav.Ar, Co.Ar, and CW.Th. In other words, the playing arm's extra bone mineral, and thus increased bone strength, was mainly due to increased bone size and not due to a change in volumetric bone density. These upper arm results may not be generalized to the entire skeleton, but the finding may give new insight into conventional dual-energy X-ray absorptiometry (DXA)-based bone density measurements when interpreting the effects of exercise on bone.